Availability and quality of emergency obstetric care in Gambia's main referral hospital: women-users' testimonies - Sundby Johanne; Cham Mamady; Vangen Siri (BMC, 2009)
Abstract Background Reduction of maternal mortality ratio by two-thirds by 2015 is an international development goal with unrestricted access to high quality emergency obstetric care services promoted towards the attainment of that goal. The objective of this qualitative study was to assess the availability and quality of emergency obstetric care services in Gambia's main referral hospital. Methods From weekend admissions a group of 30 women treated for different acute obstetric conditions including five main diagnostic groups: hemorrhage, hypertensive disorders, dystocia, sepsis and anemia were purposively selected. In-depth interviews with the women were carried out at their homes within two weeks of discharge. Results Substantial difficulties in obtaining emergency obstetric care were uncovered. Health system inadequacies including lack of blood for transfusion, shortage of essential medicines especially antihypertensive drugs considerably hindered timely and adequate treatment for obstetric emergencies. Such inadequacies also inflated the treatment costs to between 5 and 18 times more than standard fees. Blood transfusion and hypertensive treatment were associated with the largest costs. Conclusion The deficiencies in the availability of life-saving interventions identified are manifestations of inadequate funding for maternal health services. Substantial increase in funding for maternal health services is therefore warranted towards effective implementation of emergency obstetric care package in The Gambia.